Cynthia Baldwin: Improved Vaccines for the Control of East Coast Fever Inception Workshop - Baldwin, Cynthia L. (International Livestock Research Institute, 2014)
An interview with Cynthia Baldwin of the US Agency for International Development on the sidelines of an inception workshop for the Improved Vaccines of the Control of East Coast Fever in Cattle in Africa Project, held 27-29 Jan in Nairobi, Kenya.